Negara Islam ‎(Pemikiran Fikih Siyasah KH. Ibrahim Hosen)‎ - Muh Sholihuddin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
The late Ibrahim Hosen, the former mufti of MUI (Indonesian Ulama Council), was on the opinion that ceating an islamic state is obligation for muslims. This opinion is not new, considering classic Muslim jurists such as Ibn Khaldun, al-Mawardi, al-Ghazali, and Ibn Taimiyyah also held similar view. Further, Hosen argued that the obligation is not a religious duty but also a rational conclusion. This obligation necessitates the obedience of citizens towards the government as long as the lattert follow islamic guidelines on policy making and regulating.  They are a) the policy is based on consultation, b) it is executable so that citizens will not be oppressed, c)the policy should be free from harmful consequence, d) it is aimed to implement prosperity, e) it upholds justice, and f) it is not contradictory to plain stipulations of sacred texts. On that basis, the government has the right to interpred the stipulations of sacred texts which their meanings are uncertain, including to regulate areas which the sacred texts are silent. Those areas are called a) mubah bi al-juz’i wa al-kulli, such as trade and registration and  b) mubah bi al-juz’i la al-kulli, such as regulations on marriage.